Sintesis Film Tipis Tembaga Oksida Dengan Metode Sol-gel Dip-Coating Sebagai Solar Selective Absorber - Andrizal, Andrizal; Herman, Syamsu; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Solar selective absorber (SSA) is a thin film at the surface of the collector that absorbs solar radiation selectively and convert it into maximum heat energy. Solar selective absorber can be synthesized using sol-gel dip-coating method. The purpose of this research is to know the effect variation number of dipping-drying cycles to absorptance copper oxyde coating. Piecesof aluminum with size 2cm x 4cm were cleaned using a solution of phosphoric acid 10% at temperature 50oC for 10 minutes. Sol precursor prepared by disolved copper nitrate trihidrate and propionic acid in ethanol. The sol prekursor was stirred for 2 hours at room temperature. The coating was synthesized with 0.3M and the number of dipping-drying cycles 4x, 6x and 8x, then annealed at temperature 550 oC for 1 hour. The results showed that thehighest absorptance value found in coatings which was synthesized using copper oxyde 0.3M at 8x cycles with absorptance (Î±) = 71.99%, emitance (Îµ) = 6.63%, XRD test showed of cupric oxide (CuO).Keywords : coating, solar selective absorber, sol-gel dip-coating.